2022
DOI: 10.7759/cureus.24051
|View full text |Cite
|
Sign up to set email alerts
|

Brain Magnetic Resonance Imaging-Based Evaluation of Pediatric Patients With Developmental Delay: A Cross-Sectional Study

Abstract: BackgroundDevelopmental delay refers to the insufficient acquisition of age-appropriate developmental milestones. According to World Health Organization, approximately 5% of all children under the age of 14 years display some developmental disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The findings of the present study, conducted in Saudi Arabia, are in line with previous research conducted in various countries, demonstrating consistent patterns of cortical abnormalities in individuals with DD [ 12 , 34 ]. Abnormal findings on the MRI brain of patients with DD have been reported in numerous studies [ 5 , 12 , 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of the present study, conducted in Saudi Arabia, are in line with previous research conducted in various countries, demonstrating consistent patterns of cortical abnormalities in individuals with DD [ 12 , 34 ]. Abnormal findings on the MRI brain of patients with DD have been reported in numerous studies [ 5 , 12 , 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study, conducted in Saudi Arabia, are in line with previous research conducted in various countries, demonstrating consistent patterns of cortical abnormalities in individuals with DD [ 12 , 34 ]. Abnormal findings on the MRI brain of patients with DD have been reported in numerous studies [ 5 , 12 , 49 , 50 , 51 ]. These abnormalities may include cortical abnormalities, CSF alterations, dysplasia, abnormal size or signal in the basal ganglia, and anomalies in the cerebellum and brain stem [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Neuroimaging may be recommended as either a first‐ or second‐line investigation for children presenting with developmental delay with variable diagnostic yields reported, from high percentages (Ali et al, 2015; Randhawa et al, 2022), to lower diagnostic yields (Murias et al, 2017). A systematic review of MRI‐B findings reported for children with developmental delay or cognitive impairment reported a pooled diagnostic yield of 7.9%.…”
Section: Discussionmentioning
confidence: 99%